Parallel solution methods in computational mathematics - Papadrakakis, Manolis (Wiley series in solving large-scale problems in mechanics, 1997)
This book follows the previously published title, Solving Large-scale Problems in Mechanics, edited by M. Papadrakakis. This first volume to be published in the Wiley Series in Solving Large-scale Problems in Mechanics is devoted to high-performance computing using the new generation of computers with parallel and distributed computing capabilities. Parallel and distributed processing is a rapidly growing area of high technology where engineering applications lagged behind hardware advances. New algorithms and codes are required in order to exploit effectively modern computer architectures, as programs suitable for conventional computers achieve very modest performances on these new machines. There is therefore an urgent need to develop and test powerful solution and data handling techniques capable of exploiting the potential of modern computers and of accomplishing the solution of complex engineering problems in an acceptable computing time. This volume intends capturing the latest developments in the field and to serve as an essential reference book on the subject. It comprises a comprehensive state-of-the-art treatment of theory and practice, illustrated by extensive numerical examples.